Propagation Characteristics of the Rare Endemic Rhododenderon micranthum Turcz. - Sang Im Oh; Eun Hye Park; Hong Min Koh; Min Gil; Mi Jeong Yoon; Jun Kyu Bae; Chung Ho Ko (Horticulturae, 2023)
This study was conducted to examine the effect of plant growth regulators on the rooting and growth of Rhododendron micranthum Turcz., a rare plant in South Korea. Indole-3-butyric acid (IBA) 150, 250, 350 mg·L−1 and α-naphthaleneacetic acid (NAA) 50, 150, 250 mg·L−1 treatment groups were established and cutting was performed in a commercial growth medium in March 2021 with 3 replications of 10 plants per group. After 70 days, the longest initial root growth was observed under the NAA 150 and 250 mg·L−1 treatments. Moreover, the number of roots and percentage of rooting were slightly higher in NAA 150 and 250 mg·L−1, indicating that these treatments were more effective in promoting plant growth. The above-ground part of plants treated with NAA 150 and 250 mg·L−1 had a taller plant height, longer and wider leaves, and a greater number of leaves compared to other groups. Accordingly, the survival rate of plants treated with NAA 150 and 250 mg·L−1 was higher than 80%, suggesting well-established roots and excellent above-ground growth. Therefore, treatment with growth regulator NAA at 150 and 250 mg·L−1 is considered beneficial for the cutting of R. micranthum Turcz.